HUBUNGAN ANTARA KEBERSYUKURAN DAN REGULASI EMOSI DENGAN SUBJECTIVE WELL-BEING SISWA SMPN 1 PRAMBON - Yuni Sukmawati; Widyastuti Widyastuti (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Subjective well-being is very important for someone, especially for students to understand quality of life. This study aims to determine the relationship between gratitude and emotional regulation with subjective well-being of SMPN 1 Prambon. This research method is quantitative with a population of 1043 students and a sample of 285 students. Determination of the sample using proportionate stratified random sampling technique. Collecting data in this study used three measuring scales for the variables of gratitude, emotional regulation and subjective well-being. The results of this study indicate that there is a relationship between gratitude and subjective well-being (r=0.408, p=<0.001), there is a relationship between emotional regulation and subjective well-being (r=0.428, p=<0.001), and there is a significant positive relationship between gratitude and emotional regulation with subjective well-being (F= 32.314 with p=<0.001). This study adds a new variance that gratitude and emotional regulation together predict subjective well-being by 18.6%.